Medical Management with Vaginal Misoprostol Versus Surgical Management for First Trimester Pregnancy Failure - Rehana Yasmeen; Rubina Hussain (ziauddin University, 2024)
Background: The incidence of clinically recognized miscarriages remains around 10-20%.The most common type of early pregnancy failure include spontaneous abortion, anembryonic gestation and embryonic or fetal death (missed miscarriage).In this study we compared the effectiveness of vaginal misoprostol for the management of first trimester pregnancy loss in obtaining adequate evacuation of uterus as an alternative to surgical evacuation in a tertiary care hospital. Methods: This was a Quasi experimental trial conducted at Ziauddin University Hospital and the study participants were 180 women who presented with first trimester miscarriage upto 12 weeks of gestation. The women were divided into two groups according to their choice (90 women in each). Group one named Misoprostol group who received tablet Misoprostol 800mcg vaginally, two dose 6 hours apart. Group two named surgical evacuation group, who underwent surgical evacuation under general anesthesia. Results: The success rate in achieving complete evacuation of uterus was 82.8% in misoprostol group in the current study while in surgical evacuation group it was 100%.No serious side effects were encountered in misoprostol group. KEY WORDS: Misoprostol, Medical management, Miscarriage